Zika Virus Prevalence, Correlates and Preventive Behaviors: New Evidence from Survey Data - José-Raimundo Carvalho; Victor Hugo de Oliveira; Climent Quintana-Domeque (Institute of Labor Economics (IZA), 2017)
Brazilian health authorities have recommended that pregnant women take meticulous precaution to avoid mosquito bites, and use contraceptive methods to postpone/delay pregnancies. In this article, we present new estimates on the Zika virus prevalence, its correlates and preventive behaviors in the Northeast of Brazil, where the outbreak initiated, using survey data collected between March 30th and June 3rd of 2016. The target population are women aged 15-49 in the capital cities of the nine states of the Northeast region of Brazil. We find that more educated women are less likely to report suffering from Zika (or its symptoms), and more likely to avoid pregnancy in the last 12 months and being informed about the association between Zika and microcephaly. In addition, more educated women are more likely to follow preventive measures against the Zika virus: having used long and light-colored clothes, having used mosquito repellent or insecticides, having used mosquito protective screens or kept windows closed, and having dumped standing water where mosquitoes can breed.
Keywords: I1; J1; 330; flavivirus; education; information; prevention; survey data